A decennial cross-sectional review of assisted reproductive technology in a Tertiary Hospital in Southwest Nigeria - Tawaqualit Abimbola Ottun; Adeniyi Abiodun Adewunmi; Faosat Olayiwola Jinadu; Ayokunle Moses Olumodeji; Fatimat Motunrayo Akinlusi; Kabiru Afolarin Rabiu; Oluwarotimi Ireti Akinola; Adetokunbo Olusegun Fabamwo (BMC, 2023)
Abstract Background The World Health Organization recommends that Assisted Reproductive Technology be complementary to other ethically acceptable solutions to infertility. Whereas fertility centres are increasing in number in urban regions of Africa, published reports of their performance are sparse. We present a 10-year review of assisted reproductive technology performed in a public tertiary centre in Lagos, Nigeria. Methods This was a hospital-based, retrospective, cross-sectional review of 604 women, over a 10-year period that had in-vitro fertilization or in-vitro fertilization with intra-cytoplasmic sperm injection at the Institute of Fertility Medicine, Lagos State University Teaching Hospital. Data obtained were expressed in descriptive statistics and Pearson correlation was used to determine the strength of linear relationship between two continuous variables at a significance level of p < 0.05. Results The mean age of the women was of 37.7 ± 6.2 years and 89.7% had no previous parous experience. About 27.2% of the male partners had normal seminal fluid parameters while 4.6% had azoospermia. Median serum follicle stimulating hormone of the women was 8.1 IU/L and median serum anti-mullerian hormone was 6.3 pmol/L. There was weak positive correlation between age and serum follicle stimulating hormone (r = 0.306, p < 0.001); weak negative correlation between age and serum anti-mullerian hormone (r = -0.48, p < 0.001) and very weak correlation between body mass index and serum follicle stimulating hormone (r = 0.173, p = 0.011). In-vitro fertilization and intra-cytoplasmic sperm injection was the method of fertilization used in 97.4% of the cases and 81.8% of embryos formed were of good quality. Most women (94.5%) had 2 embryos transferred and 89.9% had day-5 embryo transfer done. About 1 in 4 of the women (143/604, 23.7%) had clinical pregnancy and 49.7% of women who got pregnant had delivery of a live baby at term while 11.9% had preterm delivery of a live baby. Conclusion Despite increasing use and success of assisted reproductive technology in south-western Nigeria, there is room for improvement in clinical pregnancy rates and live birth rates post- assisted reproductive technology. Complication rates are desirably low.